2018
DOI: 10.1039/c8cp00176f
|View full text |Cite
|
Sign up to set email alerts
|

Strong metal–support interaction improves activity and stability of Pt electrocatalysts on doped metal oxides

Abstract: Niobium and antimony doped tin oxide loose-tubes decorated with Pt nanoparticles present outstanding mass activity and stability, exceeding those of a reference carbon-based electrocatalyst. Physico-chemical characterisation and in particular X-ray photoelectron spectroscopy demonstrate that this observation can be ascribed to the strong metal-support interaction promoting electroactivity and Pt anchoring on doped metal oxide supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 62 publications
15
70
0
Order By: Relevance
“…Furthermore, the obtained Pt/10wt %-SnO 2 /C and Pt/20wt %-SnO 2 /C catalysts exhibits 0.5-0.55 eV higher Sn 3d 5/2 binding energy (487.2 and 487.25 eV, respectively) than pure SnO 2 nanoparticles (486.70 eV [38]) which are in good agreement with [22,27], suggesting the electron transfer from tin oxide. The SMSI effect in the prepared Pt/x-SnO2/C catalysts induced by the formation of the Pt-SnO 2 clusters in which the electron donation from the oxide to Pt metal takes place enhances electron density on the latter and providing higher activity and stability of Pt nanoparticles [27]. The obtained results confirm that the SMSI effect exists but due to the low value of Pt 4f 7/2 binding energy shift its influence is expected to be limited.…”
Section: Catalysts Characterizationsupporting
confidence: 68%
See 3 more Smart Citations
“…Furthermore, the obtained Pt/10wt %-SnO 2 /C and Pt/20wt %-SnO 2 /C catalysts exhibits 0.5-0.55 eV higher Sn 3d 5/2 binding energy (487.2 and 487.25 eV, respectively) than pure SnO 2 nanoparticles (486.70 eV [38]) which are in good agreement with [22,27], suggesting the electron transfer from tin oxide. The SMSI effect in the prepared Pt/x-SnO2/C catalysts induced by the formation of the Pt-SnO 2 clusters in which the electron donation from the oxide to Pt metal takes place enhances electron density on the latter and providing higher activity and stability of Pt nanoparticles [27]. The obtained results confirm that the SMSI effect exists but due to the low value of Pt 4f 7/2 binding energy shift its influence is expected to be limited.…”
Section: Catalysts Characterizationsupporting
confidence: 68%
“…This result confirms the electron transfer from Sn to Pt providing a more filled Pt d-band and the weaker chemisorption with oxygen-containing species, such as OH ads [22,28]. Furthermore, the obtained Pt/10wt %-SnO 2 /C and Pt/20wt %-SnO 2 /C catalysts exhibits 0.5-0.55 eV higher Sn 3d 5/2 binding energy (487.2 and 487.25 eV, respectively) than pure SnO 2 nanoparticles (486.70 eV [38]) which are in good agreement with [22,27], suggesting the electron transfer from tin oxide. The SMSI effect in the prepared Pt/x-SnO2/C catalysts induced by the formation of the Pt-SnO 2 clusters in which the electron donation from the oxide to Pt metal takes place enhances electron density on the latter and providing higher activity and stability of Pt nanoparticles [27].…”
Section: Catalysts Characterizationsupporting
confidence: 66%
See 2 more Smart Citations
“…However, the methanol crossover from anode to cathode compartment, the formation of carbon monoxide, poisoning the noble metal electrodes, and the high cost of Pt are the major problems. Therefore, massive efforts have been poured into the research and development of low‐cost and high‐efficient catalysts using nonnoble metals . The previous research has documented that the Pt surface with (110) orientation has shown the higher current density than (111) and (100) orientation.…”
Section: Introductionmentioning
confidence: 99%